The orexigenic hormone acyl-ghrelin increases adult hippocampal neurogenesis and enhances pattern separation - Amy Johnson (Psychoneuroendocrinology, 2014)
An important link exists between intact metabolic processes and normal cognitive functioning; however, the underlying mechanisms remain unknown. There is accumulating evidence that the gut hormone ghrelin, an orexigenic peptide that is elevated during calorie restriction (CR) and known primarily for stimulating growth hormone release, has important extra-hypothalamic functions, such as enhancing synaptic plasticity and hippocampal neurogenesis. The present study was designed to evaluate the long-term effects of elevating acyl-ghrelin levels, albeit within the physiological range, on the number of new adult born neurons in the dentate gyrus (DG) and performance on the Spontaneous Location Recognition (SLR) task, previously shown to be DG-dependent and sensitive to manipulations of plasticity mechanisms and cell proliferation. The results revealed that peripheral treatment of rats with acyl-ghrelin enhanced both adult hippocampal neurogenesis and performance on SLR when measured 8–10 days after the end of acyl-ghrelin treatment. Our data show that systemic administration of physiological levels of acyl-ghrelin can produce long-lasting improvements in spatial memory that persist following the end of treatment. As ghrelin is potentially involved in regulating the relationship between metabolic and cognitive dysfunction in ageing and neurodegenerative disease, elucidating the underlying mechanisms holds promise for identifying novel therapeutic targets and modifiable lifestyle factors that may have beneficial effects on the brain.